Analisis Penerapan Sekolah Ramah Anak Dalam Membentuk Kenyamanan Sekolah Di SD Negeri Soropadan Surakarta - Maharani, Sisya; Mulyono, Hadi; Istiyati, Siti (Universitas Sebelas Maret, 2021)
The child-friendly school program was created because of the importance of paying attention to the rights of children at school. The purpose of the research is to describe the implementation of child-friendly school program in SD N Soropadan. Identify the supporting factors and inhibiting factors for the implementation of child-friendly schools in SD N Soropadan. Identify the impact of child-friendly school programs on the comfort of students at school. This research uses a qualitative method with the principal, teachers, and several high grade students of SD N Soropadan as sources of informants. Methods of data collection is done by means of interviews, observation, and documentation. The results of the study based on the analysis of indicators of child-friendly schools in terms of child-friendly school policies, curriculum implementation, trained education personnel on child rights, facilities and infrastructure, and student participation community have gone quite well. The supporting factors for implementing child-friendly schools at SD Soropadan are the quality of the schools and the commitment of human resources. While the inhibiting factors are the lack of funding sources and the lack of participation of parents and the community. The existence of a child-friendly school program is very influential for the comfort of students at school because school facilities are increasingly being improved and educators are more competent in understanding children's rights.